Establishment and application of a preset dilution factor strategy for human chorionic gonadotropin testing in clinical laboratory - Chen, Shu; Li, Qin; Liao, Huaqiang; Zhao, Mingcai; Chen, Jie; Chen, Hongyu; Xiao, Guangjun (Frontiers in Molecular Biosciences, 2025)
IntroductionAutomated dilution has improved the efficiency of human chorionic gonadotropin (hCG) testing, however, challenges persist regarding the cost implications of repeated testing. This study proposes the concept of cost-effective optimization, which aims to further optimize testing efficiency while maintaining controllable costs, and establishes an automated process with preset dilution factors for the hCG testing.Materials and methodsThe hCG testing process at Suining Central Hospital was optimized using the Aptio™ Automation Solution (Siemens Healthineers, Erlangen, Germany) integrated with Siemens Atellica® IM1600 analyzer. A novel middleware program was developed within the DataLink V2.0 (Siemens Healthineers, Erlangen, Germany) to automate dilution factor assignment. Relevant data such as dilution factors, sample reception time and review time were captured for statistical purposes to analyze the accuracy, ability to shorten TAT, and economic benefits of hCG testing.ResultsAfter 8 months of continuous improvement, implementation of automated hCG dilution attained 91.19% compliance rate with 19.7% reduction in in-laboratory TAT. The process achieved 75.60% compliance against the 90 min benchmark, while the preset dilution process generated 15.03% mean cost savings per test.ConclusionIn this study, a preset dilution factor program was utilized to establish an automated dilution process, achieving accurate and rapid prediction of hCG. These strategies not only improve efficiency, but also effectively reduce costs, enabling the expansion of testing items and facilitating the implementation in laboratories. Furthermore, they also help to shorten the in-hospital TAT for patients, and improve the hospital’s service quality.